2017
DOI: 10.1186/s12943-017-0740-6
|View full text |Cite
|
Sign up to set email alerts
|

Bi-directional exosome-driven intercommunication between the hepatic niche and cancer cells

Abstract: BackgroundOur understanding of the multiple roles exosomes play during tumor progression is still very poor and the contribution of the normal tissue derived exosomes in distant seeding and tumor outgrowth has also not been widely appreciated.MethodsUsing our all-human liver microphysiological system (MPS) platform as a model to closely recapitulate the early metastatic events, we isolated exosomes from both tumor cells and liver microenvironment.ResultsWe observed that while priming of the hepatic niche (HepN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 43 publications
1
52
0
Order By: Relevance
“…Another study by Dioufa et al (2017) showed that priming the hepatic niche with exosomes exuded from MDA-231 breast cancer cells facilitated seeding of the cancer cells in the liver. Intriguingly, the same study also showed a difference in a certain set of miRNA contents in the tumour-derived exosomes compared with exosomes from normal cells (which happened to be a set of miRNAs involved in epithelial cell differentiation) [135]. It was also shown that bone-derived exosomes can stimulate proliferation in tumour cells, as well as mediate communication between cancer cells and bone cells [136].…”
Section: Exosomes Involvement In Enhancing Tumour Progression and Metmentioning
confidence: 99%
“…Another study by Dioufa et al (2017) showed that priming the hepatic niche with exosomes exuded from MDA-231 breast cancer cells facilitated seeding of the cancer cells in the liver. Intriguingly, the same study also showed a difference in a certain set of miRNA contents in the tumour-derived exosomes compared with exosomes from normal cells (which happened to be a set of miRNAs involved in epithelial cell differentiation) [135]. It was also shown that bone-derived exosomes can stimulate proliferation in tumour cells, as well as mediate communication between cancer cells and bone cells [136].…”
Section: Exosomes Involvement In Enhancing Tumour Progression and Metmentioning
confidence: 99%
“…A study on human breast cancer MDA-MB-231 cells settling into a premetastatic niche in the liver showed that exosomal communication can be bi-directional. Upon priming of HepN liver cells with cancer cell-derived exosomes, liver cells secrete exosomes that turn down migratory gene expression and induce mesenchymal-to-epithelial reverse transition (MET) in cancer cells (Dioufa, Clark, Ma, Beckwitt, & Wells, 2017). As the result of this bi-directional communication, HepN-derived exosomes enhance cancer cell seeding, but also suppress cell outgrowth, which renders cancer cells temporarily dormant once settled into their niche.…”
Section: Exosomes In Cancer: Target Tissue Biohacking and Hijacking Omentioning
confidence: 99%
“…The tumor signals that enable intercalation within a tissue (including extracellular vesicles (EV)) [30][31][32][33] leads to reverse signaling (including EV) from the receptive organ that imparts the cMErT and initial dormancy. 34,35 The state of the tumor cell in dormancy is unknown, with one model positing quiescence versus another of balanced proliferation and death. In silico modeling determined that it is highly unlikely that micrometastases exist in a state of balanced proliferation and death, but rather either grow out or enter quiescence.…”
Section: The Metastatic Cascadementioning
confidence: 99%
“…The quantitative nature of this balance is noted in tumor cells producing greater numbers of EV than the host parenchymal cells, but with this being counterbalanced by the numerically vaster numbers of host cells upon single cell seeding. 35 Similarly, the growth factor-rich milieu of tumor cells may also overwhelm the death signals from the innate immune response to foreign bodies/cells, enabling greater survival of mesenchymal aggressive tumors. This is important in studying resistance to therapy if the surviving and outgrowing 'metastatic' tumor cells have not upregulated key molecules and behaviors that normally function to enable metastatic seeding, and thus would appear as falsely sensitive growths.…”
Section: 'Inoculated' Rodent Metastasismentioning
confidence: 99%